Sosialisasi Sistem Akreditasi dan Keterbutuhan Dokumen Akreditasi Pada PKPPS Khidmatusunnah - Karsiwan Karsiwan (Universitas Pahlawan Tuanku Tambusai, 2022)
The accreditation of Islamic boarding school education units is a real effort that needs to be done by religious education providers. The purpose of this service activity is as an effort to provide understanding and awareness of the quality of Islamic boarding school educational institutions. The method used in this community service activity is the community education method by providing socialization of the importance of the accreditation document given to PKPPS Khidmatusunnah as the target of the activity. The results of this community service activity include 1) the implementation of accreditation for the PKPPS group that is included in the PKBM non-formal education category, and is included in the BAN PAUD and PNF accreditation systems in each province; 2) Socialization of the accreditation assessment system and the need for accreditation documents is expected to be able to raise awareness of the importance of accreditation in educational institutions as a form of institutional accountability to the community; 3) the need for accreditation documents as national education standards consist of eight main standards, namely content standards, graduate competency standards, process standards, educational assessment standards, facilities and infrastructure standards, educators and education personnel standards, education management standards, and education financing standards